A relação do fenômeno de ruptura hidráulica em maciços de barragens de terra e o mau funcionamento de vertedores do tipo poço - Maria da Gloria Braz de Oliveira (2003)
Knowledge of the effects of air entrainment in hydraulic structures is a matter that involves many science areas and is of a great relevance to the formulation of design and operational criteria of engineering works. The interaction between liquids and gases results in natural entrainment of air bubbles into the liquid mass, as exemplified by flow in shaft spillways, as well as in artificial aeration, when attenuation of cavitations effects is desired.bIn such a context, modeling techniques are frequently used for designing hydraulic structures. As shaft and morning glory type spillways are concerned, the air entrainment phenomenon is not perfectly known, thus implying in testing their behavior in physical models. In the order hand, the instability of earthen-filled dams as caused by hydraulic disaggregation phenomenon; these due to vibrations and highly fluctuating pressures induced by existing expansion joints along the crossing structure under inadequate hydraulic functioning, needs mathematical modeling since physical modeling of cohesive soils still shows difficulties to the represented. Several researchers have studied the problem of air entrainment in shaft spillways with both vortex type or morning glory type intakes. However, they have not attempted to relate their findings to the Soil Mechanics and geothechnical fields. Aiming to fulfill void, this work presents a methodological sequence concerned to verify the instability of earthen dams as caused by malfunctioning of shaft type hydraulic structures, with the support of a mathematical model for analyzing steady flow through saturated porous media. With the additional objective of demonstrating the feasibility of such a ethodology, its application to the Pampulha dam, located in the Brazilian city of Belo Horizonte, has been successfully implemented. Briefly, in this study the pressures as resulting from expansion joints and tunnel vibrations, have been evaluated and associated to fluctuating negative and positive pressures inside an earthen dam, subjected to a malfunctioning morning glory type spillways. The results of this research may be used to identify fatigue limits in earthen dams with a given consolidation degree, as well as to identify and to provide information on the frequency of acceptable limiting release discharges from morning glory type spillways. This will certainly help checking the adequacy of flood-reducing structural measures and, in case of catastrophic floods, the proposal of additional non-structural measures for flood mitigation.